1997
DOI: 10.1023/a:1007992806818
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sequencing of the left variable region of the L60V Vero cell-adapted strain of African swine fever virus (ASFV) showed the presence of three genes belonging to multigene family 110 (MGF110) and of a fourth unrelated gene. This gene was separated from the MGF110 genes by a region rich in direct repeats. The first MGF110 gene, V1L, with 104 codons, was only moderately related to the other two, W1L and W2L, with 124 and 80 codons, respectively. These two genes were closely related, W2L being a truncated duplicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Among the 26 genes missing from the viral genome, thirteen belong to the multigene family MGF110 (1L-14L) 9 , 10 and three to the MGF360 (1L-3L). While the specific functions of these genes are unknown 11 , it was shown that members of the MGF110 carry C-Terminal KDEL endoplasmic reticulum retention motifs and might be involved in preparing the ER for viral morphogenesis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 26 genes missing from the viral genome, thirteen belong to the multigene family MGF110 (1L-14L) 9 , 10 and three to the MGF360 (1L-3L). While the specific functions of these genes are unknown 11 , it was shown that members of the MGF110 carry C-Terminal KDEL endoplasmic reticulum retention motifs and might be involved in preparing the ER for viral morphogenesis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Those findings suggest that development of attenuated ASFV recombinant viruses by genetic manipulations of a specific gene(s) is an effective approach for vaccine development. The MGF360 and MGF505 genes exist in the highly variable left-terminal region of the ASFV genome and have been the focus of investigation since some naturally attenuated field isolates such as OURT 88/3 or NHV (37), or cell-culture adapted attenuated ASFV strains such as BA71v (15,(19)(20)(21) or ASFV-G/V110 (22), presented similar deletions in this region encompassing members of both MGFs (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Some cell culture-adapted ASFV isolates (such as the Vero celladapted Badajoz71 or Georgia07 isolates) contain gaps in the variable left-terminal region of their genomes harboring deletions that encompass several genes of both MGF360 and MGF505 (15,(19)(20)(21)(22). Usually, adaptation to replication in these cell lines coincides with attenuation of these isolates in swine (8,(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…The process of ASFV adaptation to be able to replicate in established cell lines is usually accompanied by attenuation of virulence and significant modifications of the viral genome, generally affecting the variable genomic ends (21,22,23,24,25). Unfortunately, in most of these cases, detailed descriptions of the adaptation process and the associated genetic and phenotypic changes of ASFV are not readily available.…”
Section: Discussionmentioning
confidence: 99%